Role playing a method in teaching character education to socially-alienated children (intermediate grades) - Pagal, Francisca V. (1973)
The study is an attempt to work on a curriculum material in teaching character education through role-playing. It aims to help the special education teachers in the quest for a curriculum relevant to national needs and consistent with educational goals. Aside from the task of relating concepts in Character Education to the country's needs, this paper chose role playing for the socially-alienated children. These children need a different learning approach which will give them a liberating outlook to life's situation.